Functional genomics approach for the identification of human host factors supporting dengue viral propagation - Barrows, Nicholas J. (2014)
Dengue virus (DENV) is endemic throughout tropical regions around the world and there are no approved treatments or anti-transmission agents currently available. Consequently, there exists an enormous unmet need to treat the human diseases caused by DENV and block viral transmission by the mosquito vector. RNAi screening represents an efficient method to expand the pool of known host factors that could become viable targets for treatments or provide rationale to consider available drugs as anti-DENV treatments. We developed a high throughput siRNA-based screening protocol that can identify human DENV host factors. The protocol herein describes the materials and the procedures necessary to screen a human cell line in order to identify genes which are either necessary for or restrict DENV propagation at any stage in the viral life cycle.